Nannofossil Distribution and Age of Kendeng Zone In Kalibeng River Section of Kedungringin, Plandaan Area, Jombang, East Java - Choiriah, Siti Umiyatun; Prasetyadi, Carolus; Kapid, Rubiyanto; Yudiantoro, Dwi Fitri (Geological Agency, 2020)
DOI:10.17014/ijog.7.1.15-24This study was carried out at Kalibeng River Section, in Kedungringin area, a site with lithology suitable for a nannoplankton research. Methods used in this research include performing a stratigraphical measurement section at the field, collecting thirty-two samples, and preparing the samples with the smear slide method using a polarizing microscope with 1000x magnification, and preparing several rock samples using SEM analysis. The analysis of nannofossil resulted in twelve genera and forty-three species. The identified genera are: Calcidiscus, Coccolithus, Ceratolithus, Discoaster, Gephyrocapsa, Helicosphaera, Pseudoemiliania, Reticulofenestra, Rhabdosphaera, Sphenolithus, Syracosphaera, and Umbilicosphaera. The presence of these genera indicates that Kalibeng River Section have abundant nannofossils and based on the nannofossil analysis, from older to younger, the studied stratigraphic sequence indicates a more detailed age determination as follows: the Marl Unit of Kalibeng is NN10-NN18 (Middle Miocene to Pliocene), Calcareous Sandstone Unit of Sonde is NN19-NN20 (Pliocene-Pleistocene), and Calcareous Claystone Unit of Sonde is NN20-NN21 (Pleistocene).